IMPLEMENTATION OF COMPREHENSIVE MIDWIFERY CARE - Netty Herawaty Purba; Septi Maisyaroh Ulina Panggabean; Masriani Situmorang (Bajang Institute, 2021)
The research aims: To provide comprehensive midwifery services to mothers since pregnancy, childbirth, newborns and contraception services. Research methods: The research design used is descriptive, with a clinical case study method. Research result: From the results of the assessment of Mrs. M aged 23 and the comprehensive midwifery care that had been given and it was found that everything was in normal condition. After doing Comprehensive Midwifery Care at Independent Practice Midwives/ BPM Nurkhairiyah, comprehensive midwifery care has been given. The client says he is satisfied and understands the care he has received, and provides great benefits for the client and the baby and family and for the client in providing family planning care, the client has not decided to choose a contraceptive will be used.. Conclusion: From the midwifery care obtained, the mother said she felt satisfied and appreciated, both in the care of pregnancy, childbirth, postpartum, newborn and the period of choice of using contraception. the mother feels that she can play a role in making choices regarding needs as well as in decision making. Suggestion: Midwives should be able to carry out comprehensive care on an ongoing basis so that in the hope of reducing maternal and infant mortality and morbidity, it can be achieved.